Video Edukasi Range of Motion sebagai Upaya Peningkatan Pengetahuan dan Keterampilan Family Caregiver Pasien Stroke - Putri Oktaviani Purwanto; Sodikin Sodikin (Universitas Faletehan, 2025)
Previous studies have shown that the level of family knowledge increases significantly after receiving health education about the treatment of stroke patients and the use of video media is effective in increasing family knowledge, especially on how to perform range of motion (ROM). This research aims to assess how ROM educational videos impact the knowledge and skills of family caregivers in training stroke patients. It used a pre-experiment one group pretest-posttest approach. The research sample was 50 family caregivers with stroke at Ajibarang Hospital in East Java, Indonesia, selected by purposive sampling technique. The instruments used were questionnaires and checklist sheets. ROM education was conducted once via a 10-minute video. The results were analyzed using the Wilcoxon test. The research results showed an influence of ROM educational videos on the knowledge and skills of family caregivers with a p-value = 0.001. Further research could add a comparison group and increase the frequency of the intervention. The authors recommended a regular implementation of health education using video media as part of routine educational programs in healthcare facilities. This is because videos have been proven to enhance family caregivers’ understanding by combining audio and visuals and being able to replay at any time.